ENGLISH AS A FOREIGN LANGUAGE PRESERVICE TEACHERS' EXPERIENCE IN PLAYING ONLINE GAMES FOR READING COMPREHENSION - FIKRY KHAIKAL; Ventje Jany Kalukar; Effendi Limbong (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2024)
This research was conducted to determine whether playing games affects English-speaking students, especially students' reading comprehension skills in the academic field/in the classroom. The students studied were students of the English language education program at the Faculty of English, Mulawarman University, class of 2019. This research used a mixed methods approach with a case study design. This research involved 5 English students from the English Faculty of Mulawarman University class of 2019. Mixed method data is taken from interviews and quantitative data is taken from tests as a tool to validate and convince interview data. This research found that students felt helped by playing online games and improving their English language skills, especially their ability to read and understand in class. This research also found that although in theory, online games can improve students' English skills, there are also challenges behind it all. For the students themselves, they face challenges such as unfamiliar words which make it difficult for them to understand the context/message they want to convey when reading while playing online games.